Comparison of the Success Rate of Filled and Unfilled Resin-Based Fissure Sealants: A Systematic Review and Meta-analysis - Elmira Bagheri; Alireza Sarraf Shirazi; Kiana Shekofteh (Tehran University of Medical Sciences, 2022)
Objectives: Incorporation of fillers might improve the physical properties of sealants. This systematic review and meta-analysis evaluated the retention and caries development rate of filled and unfilled fissure sealants. Materials and Methods: This study was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. The PubMed, Scopus, Embase, Cochrane Database of Systematic Reviews, and ISI Web of Knowledge were searched until October 24, 2019. The risk of bias (ROB) was assessed for the included studies based on the Cochrane collaboration common scheme for bias, and the meta-analysis was performed through a random effects model. Results: The search resulted in 6,336 unrepeated relevant studies. After the title, abstract and full-text screening, 19 studies with 26 comparing groups were finally included in this systematic review and meta-analysis. According to the included studies, both retention rate and caries development in filled and unfilled resin-based sealants did not significantly differ within 2 years of follow-up. Conclusion: Since there was no significant difference in the retention rate and caries development between filled and unfilled sealants, it seems that the final decision should be made uniquely for each patient according to the type of fissure, patient's age, habits, etc.